Titration Calorimetry From Concept to Application - Hansen, Lee D.; Transtrum, Mark K.; Quinn, Colette F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This Brief describes the calibration of titration calorimeters (ITCs) and calculation of stoichiometry, equilibrium constants, enthalpy changes, and rate constants for reactions in solution. A framework/methodology for model development for analysis of ITC data is presented together with methods for assessing the uncertainties in determined parameters and test data sets. This book appeals to beginners, as well as to researchers and professionals in the field.
Chapter1: Introduction to Calorimetry -- Chapter2: Introduction to Titration Calorimetry -- Chapter3: Determination of Equilibrium Constants by Titration Calorimetry -- Chapter4: Determination of Reaction Kinetics by Calorimetry -- Chapter5: Statistics of Curve Fitting -- Chapter6: Related Topics in Calorimetry -- Chapter7: Self-test Questions -- Chapter8: Self-test Key.
Keywords: Physical chemistry; Measurement; Measuring instruments; Medicine -- Research; Biology -- Research; Physical Chemistry; Measurement Science and Instrumentation; Biomedical Research